2018
DOI: 10.1186/s13550-018-0372-x
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of DOTA-conjugated HPMA-based polymers with trivalent metallic radionuclides for molecular imaging

Abstract: BackgroundIn this work, the in vitro and in vivo stabilities and the pharmacology of HPMA-made homopolymers were studied by means of radiometal-labeled derivatives. Aiming to identify the fewer amount and the optimal DOTA-linker structure that provides quantitative labeling yields, diverse DOTA-linker systems were conjugated in different amounts to HPMA homopolymers to coordinate trivalent radiometals Me(III)* = gallium-68, scandium-44, and lutetium-177.ResultsShort linkers and as low as 1.6% DOTA were enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…43 Sc can be produced via proton irradiation of 43 Ca or 46 Ti, as well as a-irradiation of 40 Ca or deuteron irradiation of 44 Ca (5-7). 44g,m Sc can be produced via proton irradiation of 44 Ca, 47 Ti, or 45 Sc or deuteron irradiation of 44 Ca (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Enriched targets are preferred to avoid production of contaminants such as 46,48 Sc (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Sc can be produced via proton irradiation of 43 Ca or 46 Ti, as well as a-irradiation of 40 Ca or deuteron irradiation of 44 Ca (5-7). 44g,m Sc can be produced via proton irradiation of 44 Ca, 47 Ti, or 45 Sc or deuteron irradiation of 44 Ca (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Enriched targets are preferred to avoid production of contaminants such as 46,48 Sc (18).…”
mentioning
confidence: 99%
“…In this case, the pair would be 43,44g Sc as the diagnostic agent and 47 Sc as the therapeutic agent. Studies have compared the labeling efficiencies of 68 Ga, 177 Lu, and 44g Sc for DOTA-HPMA (N-(2-hydroxypropyl) methacrylamide) conjugates and showed that the 44g Sclabeled polymer was highly stable for up to 24 h, showing promising characteristics for in vivo imaging (12). A similar study determined that reaction rates were increased when buffers including EtOH were used, allowing for lower temperatures and a reduced time to achieve labeling yields above 90% for DOTA complexes with these 3 radioisotopes (26).…”
mentioning
confidence: 99%
“…The scandium radionuclides labeled bombesin analogs (Koumarianou et al 2012), RGD peptides (Domnanich et al 2017c), folate derivatives (Muller et al 2018;Muller et al 2014;Siwowska et al 2019) and PSMA ligands (Umbricht et al 2017) have been evaluated pre-clinically. Few studies have also reported on scandium radiolabeled antibodies, antibody fragments or affibodies (Chakravarty et al 2014;Honarvar et al 2017;Moghaddam-Banaem 2012) and nanoparticles (Eppard et al 2018). A summary is given in Table 6.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…In certain cases, a reactive polymer like those containing ester groups can be functionalized with multiple ligands. For example, perfluorinated ester synthesized by controlled radical polymerization followed by postsynthesis modification can yield well‐defined, low‐dispersity, multifunctional copolymers of HPMA 144 . To reduce radiation‐induced nephrotoxicity in somatostatin receptor (SSR)‐positive tumours, a poly(lactide‐ co ‐glycolide) nanoparticle with anti‐β‐hCG antibodies and 177 Lu labelling has been successfully employed in vivo with a very high (approx.…”
Section: Different Nanoparticle Systems Used For Delivery Of Radiophamentioning
confidence: 99%